Workflows Científicos com Apoio de Bases de Conhecimento em Tempo Real - Bursztyn, Victor S.; Dias, Jonas; Mattoso, Marta (Anais do Brazilian e-Science Workshop (BreSci); 2016: Anais do X Brazilian e-Science WorkshopDO - 10.5753/bresci.2016.10009, 2016)
One major challenge in large-scale experiments is the analytical capacity to contrast ongoing results with domain knowledge. We approach this challenge by constructing a domain-specific knowledge base, which is queried during workflow execution. We introduce K-Chiron, an integrated solution that combines a state-of-the-art automatic knowledge base construction (KBC) system to Chiron, a well-established workflow engine. In this work we experiment in the context of Political Sciences to show how KBC may be used to improve human-in-the-loop (HIL) support in scientific experiments. While HIL in traditional domain expert supervision is done offline, in K-Chiron it is done online, i.e. at runtime. We achieve results in less laborious ways, to the point of enabling a breed of experiments that could be unfeasible with traditional HIL. Finally, we show how provenance data could be leveraged with KBC to enable further experimentation in more dynamic settings.